2018
DOI: 10.1007/s00339-018-2030-6
|View full text |Cite
|
Sign up to set email alerts
|

Depth-controlled laser-induced jet injection for direct three-dimensional liquid delivery

Abstract: Needle-free jet injection enables the delivery of drugs into skin or soft tissue by puncturing them with a high-velocity liquid jet. However, precise and efficient drug delivery requires generating such liquid jets with both a controlled velocity and a high throughput, which remains challenging with current spring-and gas-actuated jet injectors. Here, we propose a depth-controlled and high-throughput injection method by adapting laser-induced forward transfer (LIFT), a high-resolution two-dimensional printing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…That is why we elaborate only on the focused part of the ejected fluid because for the high material stiffnesses we are not able to generate slower tail part fast enough to penetrate in. System avoiding slow-tail are realized by a change in the generation scheme in a way the laser pulse is close to the interface like in Turkoz et al 30 , Delrot et al 16 , or Hayasaka et al 31 . In this paper we elaborate only on the critical values required to achieve certain depths without the assessment of the efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…That is why we elaborate only on the focused part of the ejected fluid because for the high material stiffnesses we are not able to generate slower tail part fast enough to penetrate in. System avoiding slow-tail are realized by a change in the generation scheme in a way the laser pulse is close to the interface like in Turkoz et al 30 , Delrot et al 16 , or Hayasaka et al 31 . In this paper we elaborate only on the critical values required to achieve certain depths without the assessment of the efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Motivation for this work ranges from the development of needle-free transdermal drug injectors [3][4][5][6][7][8][9] , "liquid scalpel" for soft tissue dissecting [10][11][12] or devices for gene delivery [13][14][15] . The main advantage lies in the smaller extent of collateral damage caused to the tissue, superior lateral precision and addressability of certain depths 16 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 Such contactless devices provide better dose control, lateral and depth localization and lower collateral damage than the needles. 12,53 In needle-free injection devices, the liquid is pushed out of the nozzle forming a thin jet, which is powerful enough to penetrate into a tissue. The actuation scheme is commonly based on a piezoactuator, [13][14][15] loaded spring, 11,16 gas cartridge, 11 voice coil actuator 17,18 or an electrical discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Laser induced cavitation has been investigated as the driving mechanism for needle-free injection systems. 12,[21][22][23][24][25][26][27][28][29][30] Tagawa et al 28 demonstrated injection with a new type of highly focused liquid microjets generated by a laser pulse focused by an optical objective from the side of a transparent nozzle. In the recent study by Krizek et al 29 this concept was elaborated on hydrogel models mimicking stiffer materials representing mechanical properties of various soft body tissues up to 0.5 MPa (e.g.…”
Section: Introductionmentioning
confidence: 99%